Normal and Abnormal Fetal Face Atlas : Ultrasonographic Features - Levaillant, Jean-Marc; Bault, Jean-Philippe; Benoit, Bernard; Couly, Gérard (Springer International Publishing : Imprint: Springer, 2017)
This atlas offers a guide to studying the fetal face by means of ultrasound analysis. It describes key phases in cranial-facial development, allowing the reader to learn the related semiology from its most simple iteration to the most complex one. The overall examination of a newborn's face offers a rich source of information and can guide the general examination. The same applies in the context of fetal ultrasound examination. The analytical study of the fetal face not only makes it possible to screen for anomalies related to the face itself, but also yields valuable insights into the brain, the limbs, and the heart. In addition, it allows ultra-sonographers to unravel the puzzle of fetal dimorphism. Written in a pedagogical style, the book guides walks the reader through the diagnostic reasoning process step by step. The authors are pioneers in this field and teach in various university and master's degree ultrasound programs. Their aim is to share with readers their diagnostic approaches and their knowledge and passion for 2D and 3D ultrasound techniques. Each chapter includes algorithms, biometry curves, and simple guidelines that allow users to go "from sign to syndrome". The first chapter, which focuses on innovative embryology adapted to the needs of ultra-sonographers, was written by Gérard Couly, a maxilla-facial surgeon and the founding father of the specialty.
Keywords: Medicine.; Human anatomy.; Obstetrics.; Radiology.; elektronické knihy; electronic books